Strategy for Strengthening Multicultural Competence of Islamic Religious Education Teachers - Halim, Abdul (Program Pascasarjana Pendidikan Islam Universitas Islam Darul Ulum Lamongan, 2024)
Teachers have a central position in education. This is inseparable from their role as the frontline in developing human resources. In the context of disruptive life and interaction patterns that lead to a borderless world order, humans who are socially capable and oriented towards world peace are needed. In this aspect, teachers who have multicultural competence and strategies to form multiculturalist educators are needed. This research is qualitative and uses a literature review approach. The data is taken from expert concepts related to the study of multiculturalism and Islamic religious education teachers. The result of the research is that multiculturalist Islamic religious education teachers are educators who have pedagogical competence, pedagogical competence, personality, professional and social as well as multicultural competence, namely competence that leads to the mastery of teachers in understanding ethnic issues, national and global values; diversity and culture. And strengthened by pedagogical skills where Islamic religious education teachers are able to sow multicultural values to their students. In the realm of strategy, a political approach to education is needed; a curriculum with multiculturalism insights and empowerment of Islamic religious education teachers